Culturally responsive and high-leverage practices: Facilitating effective instruction for English learners with learning disabilities - Wei, Yan; Hovey, Katrina A.; Gerzel-Short, Lydia; Hsiao, Yun-Ju; Miller, Rhonda D.; Kelly, Jerae H. (TESOL Journal)
Research suggests that English learners (ELs) with learning disabilities (LD) may benefit from culturally responsive evidence-based instructional approaches. ELs with LD often present with learning challenges that influence language acquisition and literacy development. One way to address the distinctive proclivities of these students is to consider the importance of culturally responsive evidence-based instruction that can elevate student understanding and academic achievement. This article explores the integration of two theoretical frameworks: culturally responsive practices and high-leverage practices. It then outlines the importance of teacher introspection as an instructional foundation and identifies several strategies for ELs with LD by centering instruction around linguistic assets and cultural values in combination with effective instructional practices. The article concludes with a call to action for teachers to tailor instruction based on students' cultural and language assets, in combination with effective instructional practices to enhance student learning.
Keywords: dept.sed; peer-reviewed